2013
DOI: 10.1590/s0036-46652013000200004
|View full text |Cite
|
Sign up to set email alerts
|

Survey of Sandfly Fauna (Diptera: Psychodidae) in Uberlândia, Minas Gerais State, Brazil, 2003-2004

Abstract: SUMMARYWe analyzed the sandflies around houses and domestic animal shelters located in residences close to forests in localities on the banks of the Araguari River, Uberlândia, MG, from February 2003 to November 2004. The phlebotomines were captured in the peridomiciliary area, where Shannon traps were utilized in the peridomicile and CDC traps in animal shelters. 2,783 specimens of sandflies were captured, 2,140 females (76.9%) and 643 males (23.1%), distributed between 17 species. The most abundant species w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…2017). Herein, we detected single infections of L. infantum , L. amazonensis and L. braziliensis , which highlights the epidemiological threat in the transmission to humans causing visceral, cutaneous and/or mucocutaneous leishmaniasis (Lemos and Lima 2005; Paula et al 2013). This work opens new perspectives to study the importance of bats in the epidemiology of leishmaniases, though the presence of amastigotes in the skin or blood of the animal has not been directly demonstrated, which would provide the greatest opportunity for phlebotomine infection.…”
Section: Discussionmentioning
confidence: 84%
“…2017). Herein, we detected single infections of L. infantum , L. amazonensis and L. braziliensis , which highlights the epidemiological threat in the transmission to humans causing visceral, cutaneous and/or mucocutaneous leishmaniasis (Lemos and Lima 2005; Paula et al 2013). This work opens new perspectives to study the importance of bats in the epidemiology of leishmaniases, though the presence of amastigotes in the skin or blood of the animal has not been directly demonstrated, which would provide the greatest opportunity for phlebotomine infection.…”
Section: Discussionmentioning
confidence: 84%
“…longipalpis is more abundant in peridomiciles, even in rural environments ( Ferreira et al 2013 , Pinheiro et al 2013 , Rêgo et al 2014 ) or in transitional secondary forest-recent deforested areas ( Pinto et al 2012 , Carvalho et al 2013a ), although the presence of forest edges close to residences was suggested as a potential shelter during the use of insecticides ( Oliveira et al 2012 ). However, bias in the actual distribution pattern of the population due to trapping designs or transitional events should be taken into account, as the absence of blood sources close to the traps could yield low capture rates in sylvatic environments ( Oliveira et al 2012 , de Campos et al 2013 , Carvalho et al 2013b , Rodrigues et al 2013 ) and so produce higher capture rates in recent human settlements with clustered blood sources ( Vilela et al 2011 , Paula et al 2013 ) or when urbanisation is ongoing simultaneously with the destruction of the original sylvatic habitats ( Lainson & Rangel 2005 , Marzochi et al 2009 , Alves et al 2012 , Queiroz et al 2012) .…”
Section: The Urbanisation-dispersion Of Lu Longipalpismentioning
confidence: 99%
“…A study evaluated the positivity rate for leishmaniasis in asymptomatic animals treated at the Veterinary Hospital of Universidade Federal de Uberlândia, from August to November 2017, and showed an infection rate of 26% (MENDONÇA, 2018). Some studies have identified the presence of disease vectors in the Araguari river basin (LEMOS;LIMA, 2005;PAULA et al, 2013), in the urban area (PAULA et al, 2008) and in Parque do Sabiá, a large park and zoo area in the East of the city (RODRIGUES et al, 2011).…”
Section: Introductionmentioning
confidence: 99%